Financial resource management in the non-profit sector: key specificities and challenges - Dragan Cvetkovic; Miljana Barjaktarovic; Tamara Vesić (BizInfo)
Non-profit sector organizations are focused on meeting their clients' needs in accordance with a clearly defined mission and set goals, without emphasizing profit. Non-profit organizations can efficiently distribute resources, maintain activities, and achieve their objectives by successfully managing their financial resources. This paper aims to highlight the need for and support more detailed research into the characteristics and models of financial resource management within the non-profit sector and its organizations, to achieve more effective management and efficient allocation of financial resources in this sector. Financial resource management is one of the most challenging areas primarily addressed by financial management. The focus of the paper is on understanding the characteristics and challenges of managing organizations that have social and/or humanitarian goals. Additionally, the goal is to emphasize the importance of applying good management practices, the need to create an adequate framework for the development of financial management in the non-profit sector, and the improvement of financial resource management models, all to enhance the quality-of-service delivery to users based on the analysis of the specificities of financial resource management.